IRMANDADE DOS COSSACOS DE PRUDENTÓPOLIS/PR: IMIGRAÇÃO, IDENTIDADE E RELIGIOSIDADE - Corrent, Nikolas (2019)
This dissertation, entitled ―Brotherhood of the Cossacks from Prudentópolis/PR: immigration, identity and religiosity‖, refers to a historical and sociocultural study carried out for understanding the creation of the Brotherhood of the Cossacks, located in the municipality of Prudentópolis/PR, and their relations with the practices, customs and traditions pointed out as constitutive elements of the descendants of Ukrainian immigrants identity in Brazilian territory. Prone to respond to certain questionings about the establishment, acting and importance of the Brotherhood in Prudentópolis, the author sets out to analyse the Ukrainians immigratory process, the setting up and the preservation of a cultural identity and the religious rituals performed by the descendants and adherents of the Ukrainian culture, noticed as the main cultural trait of the ethnic group studied. The chronological cut established, begins in 1955, when the group of guards in the municipality was created, going through 2008 with the idealization of the Brotherhood, and in 2012, the year of the Statute of the Brotherhood, and lasts until 2018. To carry out these objectives, the research took hold of theoretical, conceptual and documentary sources, congregated to the oral history methodology, through which data collection, interviews and photographs in the municipality itself were possible. As theoretical and conceptual references, the works of some authors were used, such as Stuart Hall (2002), to elucidate on the Identity, Fredrik Barth (1998) to explain ethnical boundaries and Eric Hobsbawm and Terence Ranger (1984) to define the invention of traditions. Relevant to historiography, the consultation focused in authors who approach the immigration process which led the Ukrainians to Brazil, as well as elucidate the occurrences of the installation in the new homeland. Among these authors and their works are Andreazza (1996), Boruszenko (1969), Burko (1963), Ivanchichen (2002) and Skavronski and Seniuk (2014). In order to elucidate the identity and religiosity of the Ukrainian descendants, authors such as Guérios (2012), Ramos (2006) and Tenchena (2010) were studied. The results found indicate the fact that the Brotherhood emanated of the enterprise of a Ukrainian immigrant, with the intention of carrying out the Vigil of the Holy Shroud in the Parish of Saint Josaphat. In addition, their practices derived from the religiosity, nationalism and sense of belonging of the Cossacks in the municipality. In summary, the work presents information relevant to the Ukranian immigration in Prudentópolis/PR, and also to the memory, the remembrance, the culture, the tradition, as well as the religiosity of the descendants and, above all, it tries to contribute as a source of research on the Brotherhood of the Cossacks.